Magnetic structure and manufacturing method and application thereof
Through the heating and decompression forming and pressing process, the strength and magnetic permeability of the magnetic structure in wireless charging technology are improved, and the problems of low charging efficiency and abnormal equipment operation in the prior art are solved, thereby achieving efficient and stable magnetic structure manufacturing.
Patent Information
- Application Number
- CN202311336114.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
AI Technical Summary
In the existing wireless charging technology, the strength and permeability of the magnetic structure are insufficient, resulting in low charging efficiency and abnormal equipment operation.
A special molding and pressing process of heating and reducing pressure is adopted, and granulated by mixing magnetic powder, thermosetting resin and curing agent, and pressing under constant temperature and constant pressure and continuous heating and decompression is obtained to obtain a high-strength and high magnetic permeability magnetic structure.
The molding density and strength of the magnetic structure are improved, the magnetic permeability is significantly improved, the process and power consumption is reduced, and the stability and performance of the magnetic structure are enhanced.
Smart Images

Figure CN119852077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to a magnetic structure and a manufacturing method and use thereof. Background Art
[0002] At present, with the rapid development of power electronics technology, intelligence and multi-function have become people's common pursuit. One of the important development trends is the development of wireless charging technology and its application in smart homes, the Internet of Things, mobile devices, etc.
[0003] Wireless charging technology refers to a technology that transmits power resources in the form of magnetic fields or electromagnetic waves without relying on media such as wires. It uses the basic principle of electromagnetic induction, sets coils at the sending and receiving ends, connects the wired power supply through the sending coil to generate electromagnetic signals, and the receiving coil senses the electromagnetic signals, thereby achieving power transmission.
[0004] One of the important goals of wireless charging technology development is to improve charging efficiency. Usually, the coil is embedded in a magnetic structure made of magnetic materials. At this time, the leakage magnetic flux can be effectively reduced and the electromagnetic induction efficiency can be improved. However, the induced magnetic field often causes eddy currents in the metal material, which will cause the magnetic material or coil to heat up, thereby reducing the wireless charging efficiency or causing abnormal operation. Therefore, it is necessary to use magnetic materials with high magnetic permeability and low loss coefficient to form a magnetic structure.
[0005] At present, the magnetic structure used in wireless charging technology is usually composed of soft magnetic powder and adhesive, and hot pressing or cold pressing is usually required during the molding process. Among them, hot pressing is mainly a method of heating the soft magnetic powder to a suitable temperature and then pressing the powder. For example, a hot pressing process is used in a preparation method of a soft magnetic alloy composite material disclosed in CN102964774A, and CN103862048A discloses a method for preparing a soft magnetic composite material by hot pressing. The core principle of the above hot pressing is to reduce the viscosity of the resin adhesive in the soft magnetic powder to a low level by heating, so that the molding pressure can be effectively reduced during the pressing process. However, due to the decrease in the viscosity of the resin adhesive during the pressing process, the pressure will be fully transferred to the soft magnetic powder, which will cause the soft magnetic powder to deform, thereby causing the soft magnetic powder to cause surface powder loss, cracks and other problems during the demolding process, resulting in a decrease in the strength of the magnetic structure.
[0006] Therefore, it is necessary to develop new high-strength, high-permeability magnetic structures and their manufacturing solutions to improve their stability and performance to meet their comprehensive applications in fields such as smart wearable devices. Summary of the invention
[0007] In view of the problems existing in the prior art, the object of the present invention is to provide a magnetic structure and a manufacturing method and use thereof, wherein the manufacturing method mixes magnetic powder, thermosetting resin and curing agent for granulation, performs a first pressing on the granulated material at a constant temperature and pressure, and then performs a second pressing under a state of continuous heating and decompression to obtain a magnetic structure. The method of the present invention can improve the molding morphology of the sample and improve the molding density and strength of the obtained magnetic structure through a special molding and pressing process of heating and decompression. At the same time, when the process parameters of the heating and decompression are further adapted to the characteristics of the magnetic powder, the magnetic permeability of the obtained magnetic structure can be greatly improved; the method does not use other steps such as post-heat treatment, which can effectively reduce the process and power consumption.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for manufacturing a magnetic structure, the manufacturing method comprising:
[0010] The magnetic powder, thermosetting resin and curing agent are mixed and granulated, and the granulated material is first pressed at a constant temperature and pressure, and then second pressed under a state of continuous temperature increase and pressure reduction to obtain a magnetic structure.
[0011] The method of the present invention uses a special molding and pressing process of heating and reducing pressure, which can improve density, molding flatness and strength compared with conventional cold pressing processes; compared with ordinary hot pressing processes, it can improve molding flatness, increase density and strength, and increase the molding density and strength of the resulting magnetic structure. When the process parameters of heating and reducing pressure are further adapted to the characteristics of the magnetic powder, the initial inductance (i.e., magnetic permeability) can be further greatly improved without much difference in density; the manufacturing method does not use other steps such as post-heat treatment, which can effectively reduce the number of processes and power consumption.
[0012] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] As a preferred technical solution of the present invention, the heating rate of the heating and decompression is 1 to 10°C / min, for example, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min or 10°C / min, etc., and the decompression rate is 0.01 to 0.5t / min, for example, 0.01t / min, 0.03t / min, 0.05t / min, 0.08t / min in, 0.1t / min, 0.12t / min, 0.14t / min, 0.16t / min, 0.18t / min, 0.2t / min, 0.22t / min, 0.24t / min, 0.26t / min, 0.28t / min, 0.3t / min, 0.32t / min, 0.34t / min, 0.36t / min, 0.38t / min, 0.4t / min, 0.42t / min, 0.44t / min, 0.46t / min, 0.48t / min or 0.5t / min, but are not limited to the listed values, and other values not listed in the above numerical range are also applicable. The t / min means tons per minute.
[0014] Preferably, the second pressing time is 5 to 20 min, for example 5 min, 7 min, 9 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0015] When the pressing time is the same, if the heating rate is too low, it will lead to insufficient curing, poor sample forming, and damage to demolding sampling; if the heating rate is too high, it is basically equivalent to direct high-temperature pressing, and there is no obvious effect of increasing the magnetic permeability; under the premise of the same pressing time, if the decompression rate is too high, the internal stress will be released too quickly, and the resin curing speed cannot keep up, which will affect the forming of the magnetic core and cause problems such as cracking and mold sticking; if the decompression rate is too low, it is basically equivalent to conventional hot pressing, and there is no obvious effect of increasing the magnetic permeability.
[0016] As a preferred technical solution of the present invention, the temperature of the first pressing is 120-240°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0017] Preferably, the first pressing pressure is 0.5-12 t (tons), for example, 0.5 t, 1 t, 1.5 t, 2 t, 2.5 t, 3 t, 3.5 t, 4 t, 4.5 t, 5 t, 5.5 t, 6 t, 6.5 t, 7 t, 7.5 t, 8 t, 8.5 t, 9 t, 9.5 t, 10 t, 10.5 t, 11 t, 11.5 t or 12 t, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0018] Preferably, the first pressing time is 2 to 20 min, for example 2 min, 4 min, 6 min, 8 min, 10 min, 12 min, 14 min, 16 min, 18 min or 20 min, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0019] As a preferred technical solution of the present invention, the manufacturing method includes pre-pressing the granulated material at a preheating temperature, and then performing the first pressing and the second pressing.
[0020] The present invention preferably performs pre-pressing, which can effectively improve the uniformity of the magnetic core, but has little effect on the magnetic permeability and strength.
[0021] Preferably, the preheating temperature is 80-160°C, for example 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0022] Preferably, the pre-pressing pressure is 0.2-3t, for example 0.2t, 0.4t, 0.6t, 0.8t, 1t, 1.2t, 1.4, 1.6t, 1.8t, 2t, 2.2t, 2.4t, 2.6t, 2.8t or 3t, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0023] Preferably, the pre-pressing time is 5 to 30 seconds, for example 5 seconds, 8 seconds, 11 seconds, 15 seconds, 18 seconds, 21 seconds, 24 seconds, 27 seconds or 30 seconds, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0024] Preferably, the granulated material is subjected to the pre-pressing, the first pressing and the second pressing in a mold.
[0025] Preferably, after the second pressing is completed, the mold is demoulded after cooling to ≤60°C, preferably room temperature.
[0026] As a preferred technical solution of the present invention, the magnetic powder includes iron-silicon-chromium-aluminum insulating flaky powder.
[0027] The optimization mechanism and improved effect of the above-mentioned temperature increase and pressure reduction process of the present invention are related to the powder characteristics.
[0028] Taking flaky powder as an example, at this time, when pressing under lower temperature and appropriate pressure, the fluidity of the resin before solidification can be utilized to improve the tendency of the flake powder to stack densely, improve its plastic deformation ability and strengthen the diffusion movement between particles. In the temperature rise and decompression stage, the stress in the core can be effectively removed, and the arrangement between the flake powders can be adjusted to prevent extrusion deformation after strong plastic deformation between the powders after the resin is solidified, making it more conformable to the effective magnetic circuit arrangement. Therefore, the magnetic permeability of the core can be effectively increased.
[0029] Furthermore, when the pressure of the first pressing is relatively low, the changes in the flaky powder under low pressure are similar to those of the spherical powder pressing, and the gaps between the powders become smaller, making the movement of the domain walls smoother. At this time, not only can the molding density and strength be improved, but this tight microstructure also helps to increase the magnetic permeability of the magnetic core. However, when the pressure is increased to a relatively high level, although the density and strength continue to increase, the arrangement of the flake powder is squeezed and plastically deformed, and cannot be completely arranged in the direction of the magnetic circuit. At this time, compared with the relatively low pressing pressure, the magnetic permeability of the resulting magnetic core may have a gradually decreasing trend and result.
[0030] It can be seen that for powders of different structural morphologies and sizes, the various parameters of the above-mentioned temperature increase and pressure reduction process in this case should be adapted to the characteristics of the magnetic powder to achieve the best effect of optimizing and enhancing the molding density, strength and magnetic permeability at the same time, thereby facilitating the production of high-strength, high-permeability and high-stability magnetic structures.
[0031] The magnetic powder of the present invention is preferably a flaky powder, and the flaky powder is further preferably an iron-silicon-chromium-aluminum flaky powder with better insulation and rust resistance. When a flaky powder is used, the pressure of the first pressing is preferably 0.5 to 2 t, such as 0.5 t, 0.6 t, 0.7 t, 0.8 t, 0.9 t, 1 t, 1.1 t, 1.2 t, 1.3 t, 1.4 t, 1.5 t, 1.6 t, 1.7 t, 1.8 t, 1.9 t or 2 t, etc., but is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0032] Preferably, in the iron-silicon-chromium-aluminum insulating flaky powder, the mass proportion of chromium is 0.5% to 2.5%, for example, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.1%, 2.3% or 2.5%, the mass proportion of silicon is 3% to 10%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, the mass proportion of aluminum is 3% to 10%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, and the balance is iron;
[0033] Preferably, the lateral diameter of the iron-silicon-chromium-aluminum insulating flaky powder is 10 to 30 μm, for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm or 30 μm, and the vertical thickness is 0.5 to 2 μm, for example, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm or 2 μm, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0034] High magnetic permeability has requirements for the size of magnetic powder. The longitudinal thickness will affect the forming density. Considering that ball milling process is often used to control the particle size, the transverse diameter needs to be in a suitable proportional relationship with the longitudinal thickness. In theory, the thinner the flaky powder, the better.
[0035] As a preferred technical solution of the present invention, the method for preparing the iron-silicon-chromium-aluminum insulating flaky powder includes first obtaining iron-silicon-chromium-aluminum insulating spherical powder by gas atomization, and then ball milling to obtain silicon-chromium-aluminum insulating flaky powder.
[0036] Preferably, the grinding balls of the ball mill include stainless steel balls and / or zirconium balls.
[0037] Preferably, the diameter of the grinding balls of the ball mill is 3 to 8 mm, for example 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm or 8 mm, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0038] Preferably, the ball-to-material ratio of the ball mill is 1:(8-20), such as 1:8, 1:10, 1:12, 1:14, 1:16, 1:18 or 1:20, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0039] Preferably, the solvent used in the ball milling comprises ethanol.
[0040] Preferably, the rotation speed of the ball mill is 50 to 250 r / min, for example, 50 r / min, 70 r / min, 90 r / min, 110 r / min, 130 r / min, 150 r / min, 170 r / min, 190 r / min, 210 r / min, 230 r / min or 250 r / min, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0041] Preferably, annealing treatment is performed after the ball milling.
[0042] Preferably, the annealing temperature is 600-900°C, for example 600°C, 630°C, 660°C, 690°C, 720°C, 750°C, 780°C, 810°C, 840°C, 870°C or 900°C, and the time is 0.5-3h, for example 0.5h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0043] As a preferred technical solution of the present invention, the magnetic powder is coated and modified before mixing.
[0044] Preferably, the coating modification method includes first treating with a coupling agent and then adding an insulating resin for insulation coating.
[0045] The present invention utilizes insulation modification to further enhance the insulation and rust prevention capabilities of magnetic powder.
[0046] Preferably, the coupling agent comprises any one of KH550, KH560, KH570, KH602 or KH792, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of KH550 and KH560, a combination of KH550 and KH570, a combination of KH550 and KH602, a combination of KH792 and KH550, a combination of KH560 and KH570, or a combination of KH602 and KH792.
[0047] Preferably, the coupling agent is used in an amount of 0.1% to 2% of the mass of the magnetic powder, for example, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7% or 2%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0048] Preferably, the insulating resin comprises any one of silicone resin, epoxy resin, acrylic resin, unsaturated polyester resin or phenolic resin, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of silicone resin and epoxy resin, a combination of silicone resin and acrylic resin, a combination of unsaturated polyester resin and silicone resin, a combination of silicone resin and phenolic resin, a combination of epoxy resin and acrylic resin, a combination of epoxy resin and unsaturated polyester resin, a combination of epoxy resin and phenolic resin, a combination of acrylic resin and unsaturated polyester resin, a combination of acrylic resin and phenolic resin, or a combination of unsaturated polyester resin and phenolic resin.
[0049] Preferably, the amount of the insulating resin is 0.1% to 2% of the mass of the magnetic powder, for example 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7% or 2%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0050] Preferably, the solvent used for the coating modification includes any one of isopropanol, ethanol, acetone or deionized water or a combination of at least two thereof, and typical but non-limiting examples of the combination include a combination of isopropanol and ethanol, a combination of isopropanol and acetone, a combination of isopropanol and deionized water, a combination of ethanol and acetone, a combination of ethanol and deionized water, or a combination of acetone and deionized water.
[0051] As a preferred technical solution of the present invention, the thermosetting resin includes any one of silicone resin, epoxy resin, acrylic resin, unsaturated polyester resin or phenolic resin, or a combination of at least two of the combinations. Typical but non-limiting examples of the combinations include a combination of silicone resin and epoxy resin, a combination of silicone resin and acrylic resin, a combination of unsaturated polyester resin and silicone resin, a combination of silicone resin and phenolic resin, a combination of epoxy resin and acrylic resin, a combination of epoxy resin and unsaturated polyester resin, a combination of epoxy resin and phenolic resin, a combination of acrylic resin and unsaturated polyester resin, a combination of acrylic resin and phenolic resin, or a combination of unsaturated polyester resin and phenolic resin.
[0052] Preferably, the amount of the thermosetting resin is 1% to 10% of the mass of the magnetic powder, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0053] Preferably, the curing agent includes any one of an aliphatic amine curing agent, an aromatic amine curing agent, an amine-modified curing agent, a polyamide curing agent or an anhydride curing agent, or a combination of at least two thereof. Typical but non-limiting examples of the combination include a combination of an aliphatic amine curing agent and an aromatic amine curing agent, a combination of an aliphatic amine curing agent and an amine-modified curing agent, a combination of an aliphatic amine curing agent and a polyamide curing agent, a combination of an aliphatic amine curing agent and an anhydride curing agent, a combination of an aromatic amine curing agent and an amine-modified curing agent, a combination of an aromatic amine curing agent and a polyamide curing agent, a combination of an aromatic amine curing agent and an anhydride curing agent, or a combination of a polyamide curing agent and an anhydride curing agent.
[0054] Exemplarily, the aliphatic amine curing agent includes ingredients such as ethylenediamine and diethylenetriamine; the aromatic amine curing agent includes ingredients such as meta-phenylenediamine and meta-phenylenediamine; the amine-modified curing agent can be selected from R-2257, R-2257K, etc.; the polyamide curing agent includes polyamide 650, polyamide 651, etc., and the acid anhydride curing agent includes phthalic anhydride, tetrahydrophthalic anhydride, etc.
[0055] Preferably, the amount of the curing agent is 0.1% to 2% of the mass of the magnetic powder, for example 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7% or 2%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0056] Preferably, the mixed solvent includes any one of isopropanol, ethanol, acetone or deionized water, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of isopropanol and ethanol, a combination of isopropanol and acetone, a combination of isopropanol and deionized water, a combination of ethanol and acetone, a combination of ethanol and deionized water, or a combination of acetone and deionized water.
[0057] Exemplarily, the manufacturing method of the magnetic structure described in the present invention includes the following steps: weighing magnetic powder, thermosetting resin and curing agent according to the total mass as 100%, wherein the thermosetting resin accounts for 2% to 10% of the total mass, and the curing agent accounts for 0.2% to 1% of the total mass, placing them in a mixed solvent containing acetone, and the amount of the mixed solvent is 10% to 20% of the above total mass, stirring them evenly into a transparent liquid, and then adding magnetic powder, stirring evenly until the fragments are slightly wet and sieved through 40 mesh, the sieved powder is kept at 50°C for 40 minutes, and sieved again through 40 mesh to obtain granulated material.
[0058] In a second aspect, the present invention provides a magnetic structure obtained using the manufacturing method described in the first aspect.
[0059] In a third aspect, the present invention provides a use of the magnetic structure described in the second aspect, wherein the use includes wireless charging.
[0060] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0061] The method of the present invention uses a special molding and pressing process of heating and reducing pressure, which can improve density, molding flatness and strength compared with conventional cold pressing processes; compared with ordinary hot pressing processes, it can improve molding flatness, increase density and strength, and increase the molding density and strength of the resulting magnetic structure. When the process parameters of heating and reducing pressure are further adapted to the characteristics of the magnetic powder, the initial inductance (i.e., magnetic permeability) can be further greatly improved without much difference in density; the manufacturing method does not use other steps such as post-heat treatment, which can effectively reduce the number of processes and power consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 and Figure 2 This is a microscopic morphology of the magnetic structure obtained in Example 1;
[0063] Figure 3 and Figure 4 This is a microscopic morphology of the magnetic structure obtained in Example 2;
[0064] Figure 5 and Figure 6 This is a microscopic morphology of the magnetic structure obtained in Example 3;
[0065] Figure 7 Magnetic permeability and density diagrams of the magnetic structures obtained in Examples 1-6. DETAILED DESCRIPTION
[0066] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0067] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0068] Example 1
[0069] This embodiment provides a method for manufacturing a magnetic structure, the manufacturing method comprising the following steps:
[0070] (1) preparing an iron-silicon-chromium-aluminum insulating spherical powder by gas atomization, wherein the mass proportion of chromium is 1.5%, silicon is 6.5%, aluminum is 6%, and iron is 86%; using a stainless steel ball with a ball diameter of 5 mm, controlling the ball-to-material ratio to be 1:10, adding industrial anhydrous ethanol, ball milling the obtained spherical powder at a speed of 120 r / min for 7 h, and then annealing at 750° C. for 2 h to obtain an iron-silicon-chromium-aluminum insulating flaky powder with a lateral diameter of 20 μm and a vertical thickness of 1 μm;
[0071] (2) mixing iron silicon chromium aluminum insulating flaky powder, coupling agent KH550 accounting for 1.4% of the mass of the iron silicon chromium aluminum insulating flaky powder, solvent ethanol and water (volume ratio 3:2), controlling the solvent to account for 12% of the mass of the iron silicon chromium aluminum insulating flaky powder, and then adding 1% of the mass of the iron silicon chromium aluminum insulating flaky powder to the mixture to obtain an insulating coated modified iron silicon chromium aluminum insulating flaky powder;
[0072] (3) mixing the insulating coated modified iron silicon chromium aluminum insulating flake powder, epoxy resin, aromatic amine curing agent, and solvents acetone and isopropyl alcohol, wherein the amounts of epoxy resin and aromatic amine curing agent are controlled to be 1% and 0.2% of the mass of the insulating coated modified iron silicon chromium aluminum insulating flake powder, respectively, and granulating to obtain granulated material;
[0073] (4) The obtained granules are filled into a mold, the mold is preheated to 130°C, and pre-pressed at a pressure of 0.5t for 5s;
[0074] (5) Raise the mold temperature to 150°C, keep the temperature constant (±5°C) and start pressing. Under a pressure of 2t, maintain the pressure for the first pressing for 5min, then increase the temperature at a rate of 3°C / min, and reduce the pressure at a rate of 0.2t / min. During the process of increasing the temperature and reducing the pressure, perform the second pressing for 5min.
[0075] (6) After the pressing is completed, the mold is demolded when it cools down to about 60° C. for 20 minutes to obtain a magnetic structure.
[0076] Example 2
[0077] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that the pressure of the first pressing is adjusted from 2t to 1t in step (5).
[0078] Example 3
[0079] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that the pressure of the first pressing is adjusted from 2t to 4t in step (5).
[0080] Example 4
[0081] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that the pressure of the first pressing is adjusted from 2t to 6t in step (5).
[0082] Example 5
[0083] This embodiment provides a method for manufacturing a magnetic structure. Except for adjusting the first pressing pressure from 2t to 8t in step (5), other conditions are exactly the same as those in Embodiment 1.
[0084] Example 6
[0085] This embodiment provides a method for manufacturing a magnetic structure. Except for adjusting the first pressing pressure from 2t to 9t in step (5), other conditions are exactly the same as those in embodiment 1.
[0086] Example 7
[0087] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that the pressure of the first pressing is adjusted from 2t to 12t in step (5).
[0088] Example 8
[0089] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that the pressure of the first pressing is adjusted from 2t to 13t in step (5).
[0090] Example 9
[0091] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method has the same conditions as in Embodiment 1 except that in step (5), the heating rate is adjusted from 3°C / min to 1°C / min.
[0092] Example 10
[0093] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method has the same conditions as in Embodiment 1 except that in step (5), the heating rate is adjusted from 3°C / min to 2°C / min.
[0094] Embodiment 11
[0095] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method has the same conditions as in Embodiment 1 except that in step (5), the heating rate is adjusted from 3°C / min to 5°C / min.
[0096] Example 12
[0097] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method has the same conditions as in Embodiment 1 except that in step (5), the heating rate is adjusted from 3°C / min to 6°C / min.
[0098] Example 13
[0099] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that in step (5), the decompression rate is adjusted from 0.2 t / min to 0.01 t / min.
[0100] Embodiment 14
[0101] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that in step (5), the decompression rate is adjusted from 0.2 t / min to 0.3 t / min.
[0102] Embodiment 15
[0103] This embodiment provides a method for manufacturing a magnetic structure. The manufacturing method is exactly the same as that of Embodiment 1 except that in step (5), the decompression rate is adjusted from 0.2 t / min to 0.5 t / min.
[0104] Comparative Example 1
[0105] This comparative example provides a method for manufacturing a magnetic structure, wherein the manufacturing method does not use a temperature increase and pressure reduction process in step (5), that is, step (5) is: raising the mold temperature to 150°C, keeping the temperature constant (±5°C) and starting pressing, and maintaining the pressure at a pressure of 2t for 5 minutes for the first pressing. Except for the above, the other conditions are exactly the same as those in Example 1.
[0106] Comparative Example 2
[0107] This comparative example provides a method for manufacturing a magnetic structure, wherein the manufacturing method does not use a temperature increase and pressure reduction process in step (5), that is, step (5) is: raising the mold temperature to 150°C, keeping the temperature constant (±5°C) and starting pressing, and maintaining the pressure at a pressure of 2t for 10 minutes for the first pressing. Except for the above, the other conditions are exactly the same as those in Example 1.
[0108] Ⅰ. The microstructure of the magnetic structure obtained in Examples 1-3 was tested using a Phenom XL scanning electron microscope:
[0109] Figure 1This is a top view of the outer surface of the magnetic structure (magnetic core) obtained in Example 1. Figure 2 It is a cross-sectional view, from which it can be seen that the pressing is dense and uniform, the flake powder is arranged neatly, conforming to the arrangement of the magnetic circuit (the longitudinal direction is the magnetic circuit direction), and the resin is evenly distributed; Figure 3 This is a top view of the outer surface of the magnetic core obtained in Example 2. Figure 4 It is a cross-sectional view, which shows that the pressing is dense and uniform, the arrangement of the flake powder complies with the direction of the magnetic circuit, and the resin distribution is relatively uniform; Figure 5 This is a top view of the outer surface of the magnetic core obtained in Example 3. Figure 6 It is a cross-sectional view, which shows that the pressing is dense and uniform, the arrangement of the flake powder conforms to the direction of the magnetic circuit, and the resin distribution is relatively uniform.
[0110] Ⅱ. The density, magnetic permeability and strength of the magnetic cores obtained in the embodiments and comparative examples were tested:
[0111] Density test method: measure the volume (caliper), weigh the mass with an electronic scale with an accuracy of 0.01, and calculate;
[0112] Strength test method: Use a force display universal testing machine to test the tensile strength;
[0113] Magnetic permeability test method: MICROTEST 6632 impedance analyzer is used to measure the inductance of the wound magnetic ring. 0.3mm diameter enameled copper wire is used to wind 20 turns. The test frequency is 100kHz, the voltage is 1V, and the test temperature is room temperature 25℃. The initial inductance L tested without DC bias is used to calculate the magnetic permeability μ. The calculation formula is as follows:
[0114]
[0115] Among them, le is the effective magnetic circuit length, N is the number of turns of the winding, and Ae is the effective magnetic circuit cross-sectional area.
[0116] The results are recorded in Table 1.
[0117] Table 1
[0118] Group <![CDATA[Density (g / cm 3 )]]> Magnetic permeability (H / m) Strength (kgf) Example 1 5.3 152.6 46.4 Example 2 5.2 151.4 45.7 Example 3 5.5 130.1 48.0 Example 4 5.6 119.7 50.0 Example 5 5.6 108.0 50.3 Example 6 5.7 101.5 52.8 Example 7 5.8 99.1 53.3 Example 8 5.7 95.4 53.1 Example 9 5.2 150.3 45.6 Example 10 5.3 151.2 45.8 Embodiment 11 5.1 148.6 46.2 Example 12 5.1 147.9 46.3 Example 13 5.2 149.6 46.2 Embodiment 14 5.0 137.8 44.4 Embodiment 15 4.9 132.5 42.5 Comparative Example 1 4.9 130.1 41.4 Comparative Example 2 5.2 131.0 42.3
[0119] Figure 7 is a graph showing the change in magnetic permeability and density of the magnetic structure obtained in Examples 1-6, from Figure 7As can be seen from Table 1, due to the characteristics of flake powder, at low pressure, the density and magnetic permeability increase with increasing pressure. After the pressure exceeds 2t, the density continues to increase, but the magnetic permeability decreases. The reason is that the change under low pressure is similar to the compression of spherical powder, and the gap between the powders becomes smaller, which makes the movement of the domain wall smoother. This compact microstructure helps to increase the magnetic permeability of the magnetic core. After high pressure, although the density continues to increase, the arrangement of the flake powder is squeezed and plastically deformed, and it cannot be arranged completely in the direction of the magnetic circuit, so the magnetic permeability continues to decrease. In the process of temperature rise and decompression, the faster the temperature rises, the faster the resin solidifies, resulting in too fast forming and hardening, and the powder sheets have no time to adjust their arrangement, so the magnetic permeability will be reduced. The slower temperature rise has a smaller impact, and the temperature change accuracy requirement is not high; the decompression rate decreases, the powder sheet arrangement is not fully adjusted, and the magnetic permeability will be reduced. If the decompression rate is too fast, the magnetic permeability will decrease more, and the powder sheet forming time will not be sufficient, because the powder has no pressure in the process of diffusion and dense packing with smaller gaps and contact deformation, and the forming is affected, so the magnetic permeability and density are reduced. The decompression process is also a process of ensuring a certain pressure, and the density has a great impact. The strength is basically affected by the forming density, and the higher the density, the higher the strength.
[0120] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0121] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0122] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0123] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for manufacturing a magnetic structure, characterized in that: The manufacturing method comprises: The magnetic powder, thermosetting resin and curing agent are mixed and granulated, and the granulated material is first pressed at a constant temperature and pressure, and then second pressed under a state of continuous temperature increase and pressure reduction to obtain a magnetic structure.
2. The manufacturing method according to claim 1, characterized in that: The heating rate of the heating and decompression is 1-10°C / min, and the decompression rate is 0.01-0.5t / min; Preferably, the second pressing time is 5 to 20 minutes.
3. The manufacturing method according to claim 1 or 2, characterized in that: The temperature of the first pressing is 120-240°C; Preferably, the first pressing pressure is 0.5-12t; Preferably, the first pressing time is 2 to 20 minutes.
4. The manufacturing method according to any one of claims 1 to 3, characterized in that: The manufacturing method comprises: firstly pre-pressing the granulated material at a preheating temperature, and then performing the first pressing and the second pressing; Preferably, the preheating temperature is 80-160°C; Preferably, the pre-pressing pressure is 0.2-3t; Preferably, the pre-pressing time is 5 to 30 seconds; Preferably, the granulated material is subjected to the pre-pressing, the first pressing and the second pressing in a mold; Preferably, after the second pressing is completed, demoulding is performed after cooling to room temperature.
5. The manufacturing method according to any one of claims 1 to 4, characterized in that: The magnetic powder includes iron-silicon-chromium-aluminum insulating flake powder; Preferably, in the iron-silicon-chromium-aluminum insulating flaky powder, the mass proportion of chromium is 0.5% to 2.5%, the mass proportion of silicon is 3% to 10%, the mass proportion of aluminum is 3% to 10%, and the balance is iron; Preferably, the iron-silicon-chromium-aluminum insulating flaky powder has a transverse diameter of 10 to 30 μm and a vertical thickness of 0.5 to 2 μm.
6. The manufacturing method according to claim 5, characterized in that: The method for preparing the iron-silicon-chromium-aluminum insulating flaky powder comprises firstly obtaining the iron-silicon-chromium-aluminum insulating spherical powder by gas atomization method, and then ball milling to obtain the silicon-chromium-aluminum insulating flaky powder; Preferably, the grinding balls of the ball mill include stainless steel balls and / or zirconium balls; Preferably, the diameter of the grinding balls of the ball mill is 3 to 8 mm; Preferably, the ball-to-material ratio of the ball mill is 1:(8-20); Preferably, the solvent used in the ball milling comprises ethanol; Preferably, the rotation speed of the ball mill is 50 to 250 r / min; Preferably, the ball milling is followed by annealing; Preferably, the annealing temperature is 600-900° C. and the time is 0.5-3 h.
7. The manufacturing method according to any one of claims 1 to 6, characterized in that: The magnetic powder is coated and modified before mixing; Preferably, the coating modification method includes first treating with a coupling agent and then adding an insulating resin for insulation coating; Preferably, the coupling agent includes any one of KH550, KH560, KH570, KH602 or KH792 or a combination of at least two thereof; Preferably, the coupling agent is used in an amount of 0.1% to 2% of the mass of the magnetic powder; Preferably, the insulating resin includes any one of silicone resin, epoxy resin, acrylic resin, unsaturated polyester resin or phenolic resin, or a combination of at least two thereof; Preferably, the amount of the insulating resin is 0.1% to 2% of the mass of the magnetic powder; Preferably, the solvent used for the coating modification includes any one of isopropanol, ethanol, acetone or deionized water, or a combination of at least two thereof.
8. The manufacturing method according to any one of claims 1 to 7, characterized in that: The thermosetting resin includes any one of silicone resin, epoxy resin, acrylic resin, unsaturated polyester resin or phenolic resin, or a combination of at least two thereof; Preferably, the amount of the thermosetting resin is 1% to 10% of the mass of the magnetic powder; Preferably, the curing agent includes any one or a combination of at least two of aliphatic amine curing agents, aromatic amine curing agents, amine-modified curing agents, polyamide curing agents or acid anhydride curing agents; Preferably, the amount of the curing agent is 0.1% to 2% of the mass of the magnetic powder; Preferably, the mixed solvent includes any one of isopropanol, ethanol, acetone or deionized water, or a combination of at least two thereof.
9. A magnetic structure, characterized in that: The method is obtained by using the manufacturing method described in any one of claims 1 to 8.
10. Use of the magnetic structure according to claim 9, characterized in that: Said uses include wireless charging.
Citation Information
Patent Citations
Manufacturing method of soft magnetic alloy composite material
CN102964774A
Method for preparing soft magnetic composite material through hot pressing
CN103862048A